Placement and Restoration of Dental Implants in a Patient with Paget’s Disease in Remission: Literature Review and Clinical Report - Jonathan M. Rasmussen, DDS1 & Matthew L. Hopfensperger, DDS, MS2 (Journal of Prosthodontics, 2008)
Paget’s disease is a disorder of bone that results in the replacement of normal bone with highly vascularized, low density bone